Employability potential of students of San Marcos - León Mendoza, Juan (2014)
This article aims to develop a UNMSM student population employability index by identifying the main conditioning factors affecting their probability of getting employed.Thus, the results show that the mean potential employability index of the UNMSM students stands at 55.51%.The economical regression was made through the probit model method, and the traits assessed were their marks arithmetic mean, responsibility, ease of use of informatics software, job finding skills, work experience, the own perception of their resume to satisfy adequately the general requirements of the market and, overall empathy with their colleagues. We found that there exists a clear correlation with being over the average at this traits and a higher chance of getting employed.